(untitled) (Journal of Economic Research & Business Administration, 2020)
The modern world is developing dynamically, which is facilitated by changes in technology, preferences and tastes of consumers, in business models, etc. Companies and even entire sectors of the economy have to quickly adapt to various changes in market conditions in order not only to be competitive, but also to survive in the face of uncertainty. The aim of this work is to analyze publications on the experience of adapting companies to determine the key factors of this dynamic process, as well as justify the need to develop the theoretical foundations of an adaptive economy model. It is the adaptability of economies that becomes a key condition for the well-being of society. Thus, the main areas of research are the identification of key factors in the adaptation of companies, industries and the economy as a whole to changes in economic conditions. The research methodology is the analysis and synthesis of scientific publications. Particular attention is paid to such factors as corporate culture, business model and economic institutions. The scientific and practical significance of the work is to identify the dependence of the adaptability of the economy on the adaptability of entrepreneurship (companies, organizations). The main results of the work can be used to create the theoretical base of the adaptive economy model. It is this model that meets the characteristics of dynamically changing external and internal economic conditions of entrepreneurship.